2017
DOI: 10.1111/bdi.12532
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent linear change in cognition between individuals with bipolar disorder and healthy controls over 5 years

Abstract: Objectives Cognitive dysfunction is a key feature of bipolar disorder (BD). However, not much is known about its temporal stability, as some studies have demonstrated a neurodegenerative model in BD while others have shown no change in cognitive functioning over time. Building upon our prior work which examined the natural course of executive functioning, the current study aimed to investigate the natural course of memory, emotion processing, and fine motor dexterity over a five year period in BD and healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 43 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…On the other hand, a number of recent reports that were not included in the above cited meta‐analysis also provide support claim to the hypothesis of no cognitive deterioration in middle‐life BD patients. Ryan et al reported ‐ in their cohort of middle‐aged BD patients ‐ a stability in the neuropsychological performance in the domains of visual memory, verbal memory, and emotion processing during a five‐year follow‐up period . Similarly, Sagar et al reported no deterioration in neuropsychological performance with slight improvement over time during a one‐year follow‐up period .…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, a number of recent reports that were not included in the above cited meta‐analysis also provide support claim to the hypothesis of no cognitive deterioration in middle‐life BD patients. Ryan et al reported ‐ in their cohort of middle‐aged BD patients ‐ a stability in the neuropsychological performance in the domains of visual memory, verbal memory, and emotion processing during a five‐year follow‐up period . Similarly, Sagar et al reported no deterioration in neuropsychological performance with slight improvement over time during a one‐year follow‐up period .…”
Section: Discussionmentioning
confidence: 97%
“…Forty-one studies examined facial expression recognition in samples with either remitted patients (k=20 studies; n=1026 BD, n=1144 HC) 16,24,33,34,38,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] , symptomatic patients (k=3 studies; n=97 BD, n=93 HC) 33,60,61 , mixed patient groups (i.e., patients in different episodes) with a separate analysis on each patient group (k=4 studies; n=243 BD, n=221 HC) 32,35,62,63 , mixed patient groups (i.e., patients in different episodes) with no separate analysis for each patient group (k=8 studies; n=277 BD, n=400 HC) 25,[64][65][66][67][68][69][70] , or where current episode was not specified (k=6 studies; n=364 BD, n=231 HC) [71][72][73][74][75][76] . The total sample size was n=1969 BD and n=2039 HC, with samples of individual studies ranging from n=34-628 (see Table 1).…”
Section: Studies Of Facial Expression Recognitionmentioning
confidence: 99%
“…Finally, fourteen studies were conducted in mixed samples (i.e., patients presenting with either manic or depressive symptoms or who were in remission) with no separate analysis of each patient group or where the current mood episode was not specified 25,[64][65][66][67][68][69][70][71][72][73][74][75][76] . Of these, eight found a broad facial emotion recognition deficits 25,64,65,[68][69][70]72,75 , while two studies reported selectively impaired recognition of fearful, sad 66 , or surprised expressions 74 .…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Fifteen studies compared the long-term course (⩾5 years) of cognition in BD patients with that of healthy individuals and are synthesized in Table 1. Five studies were not included in the meta-analysis due to overlapping sample with other reports (Jiménez-López et al, 2019;Mora, Portella, Forcada, Vieta, & Mur, 2016;Ryan et al, 2016Ryan et al, , 2017Santos et al, 2014). Finally, 10 studies were included in the quantitative analysis and involved 540 BD patients and 644 healthy controls (mean follow-up period: 8.9 years).…”
Section: Resultsmentioning
confidence: 99%